An Antimony(III) Fluoride Oxalate with Large Birefringence. Issue 14 (5th February 2021) - Chen, Yangxin; Chen, Zhangxian; Zhou, Yang; Li, Yanqiang; Liu, Youchao; Ding, Qingran; Chen, Xin; Zhao, Sangen; Luo, Junhua
Abstract: Birefringent materials play a key role in modulating the polarization of light and thus in optical communication as well as in laser techniques and science. Designing new, excellent birefringent materials remains a challenge. In this work, we designed and synthesized the first antimony(III) fluoride oxalate birefringent material, KSb2 C2 O4 F5, by a combination of delocalized π‐conjugated [C2 O4 ] 2− groups, stereochemical active Sb 3+ cations, and the most electronegative element, fluorine. The [C2 O4 ] 2− groups are not in an optimal arrangement in the crystal structure of KSb2 C2 O4 F5 ; nonetheless, KSb2 C2 O4 F5 exhibits a large birefringence (Δ n =0.170 at 546 nm) that is even better than that of the well‐known commercial birefringent material α‐BaB2 O4, even though the latter features an optimal arrangement of π‐conjugated [B3 O6 ] 3− groups. Based on first‐principles calculations, this prominent birefringence should be attributed to the alliance of planar π‐conjugated [C2 O4 ] 2− anions, highly distorted SbO2 F2 and SbOF3 polyhedra with a stereochemically active lone pair. The combination of lone‐pair electrons and π‐conjugated systems boosts the birefringence to a large extent and will help the development of high‐performance birefringent materials. Abstract : A synergistic combination of different functional groups has led to the first antimony(III) fluoride oxalate material, KSb2 C2 O4 F5, to exhibit a birefringent response (Δ n =0.170 at 546 nm); this value is larger than that of the commercial α‐BaB2 O4, despite its suboptimal anisotropic structure.